IMPROVING STUDENT'S PROBLEM SOLVING BY USING WORKED EXAMPLE IN THE CONTEXT OF WONOSOBO LOCAL WISDOM - Kholifatul Azizah; Nugroho Prasetya Adi (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
This research regarding applying science-worked examples in the context of local wisdom to improve students' problem-solving abilities is motivated by students' low problem-solving abilities, especially in science-physics learning. Students' standard problem-solving abilities are due to the lack of practice in the learning process. Through the application of Science Worked Examples, it is hoped that it will be able to help students in the learning process so that they can grow students' problem-solving abilities. The type of research used in this research is a quantitative method with an experimental approach. The subjects used in this research were class VIII A as a control sample and class VIII B as a testing sample at SMP N 2 Garung. The research results showed an increase of 31.9% in the control sample using conventional teaching materials and a rise of 44.1% in the experimental sample using Science Worked Examples. The effectiveness obtained using the N-Gain test was 1.38, so it was concluded that there was a difference in effective improvement where learning with worked example science teaching materials was stated to be more effective.